Transport into the south polar vortex in early spring - Hartmann, D. L.; Heidt, L. E.; Loewenstein, M.; Podolske, J. R.; Vedder, J. (1989)
The effect of transport on the springtime decline in ozone in the southern polar vortex was investiated using data on long-lived gas tracers (N2O, CH4, CCl4, CH3CCl3, CO, CFC-11, CFC-12, and CFC-113) obtained by the ER-2 aircraft in the period between August 23 and September 22 during the Airborne Antarctic Ozone Experiment. It was found that, while the concentrations of long-lived trace gases remained relatively constant for fixed potential temperature and latitude, the ozone mixing ratio over the same period declined by more than 50 percent inside the polar vortex near 18-km altitude. These data indicate a substantial photochemical sink of ozone. The evidence of the zero or negative time tendencies for long-lived trace gases and the meridional and vertical gradients of ozone imply that transport is supplying ozone to the polar region during springtime.